Can an emission trading policy promote green transformation of regional economies?: evidence from China - Jiali Qian; Yinxiang Zhou (Journal of Water and Climate Change, 2024)
To promote the green development of the global economy and solve the global energy and climate problems, the green transformation of the regional economy is the only way to solve development challenges. Carbon emission trading policies, as an important market mechanism for promoting carbon emission reduction, can further promote green economic development. This study takes the pilot carbon emission trading policy in China as a natural experiment to explore the impact of the carbon emission trading policy on the green transformation of the regional economy and its mechanism. This study accurately measures the efficiency of green transformation of the regional economy. The empirical results indicate that the carbon emission trading policy can promote the green transformation of the regional economy; carbon emission trading policies affect the green transformation of the regional economy through energy structure, urbanization level, and the interaction between energy structure and urbanization level; the model results are robust. Moreover, due to regional differences in original resource endowments, the effect of carbon emission trading policy on regional economic green transformation presents heterogeneity. Therefore, certain policy recommendations can promote the green development of the regional economy, which has important implications for interdisciplinary research, solving energy and climate problems, and high-quality growth of the world economy. HIGHLIGHTS This study adopts Super-SBM to measure green transformation.; Emission trading policies can promote the green transformation of the economy.; The effect of different regions presents heterogeneity.; Energy structure, urbanization level, and their interaction are mediating variables.;